SHARING OF RISK PADA ASURANSI SYARIAH (TAKAFUL): PEMAHAMAN KONSEP DAN MEKANISME KERJA - Netta Agusti (Jurnal MD, 2017)
This paper aims to see how the concept and mechanism of sharing of risk on Takaful Insurance. Secondary data has been used such as books and journals of Takaful, daily news, and insurance policies. As an alternative form of conventional insurance-based insurance, Takaful is able to neutralize the contradictions of existing concepts in conventional insurance, so it is acceptable and not contrary to existing sharia principles. This study explains uncertainty that occurs in the future towards the soul as well as the asset requires people to be more alert about the risks that may arise. The need for it makes insurance a financial necessity in the context of minimizing possible risks. The risk that befell the participants of the insurance, not only borne by the company alone, but by all participants Takaful Insurance, this becomes one of the differentiator between Takaful with the conventional insurance.